Prevalence of tuberculosis, HIV, and TB-HIV co-infection among pulmonary tuberculosis suspects in a predominantly pastoralist area, northeast Ethiopia - Mulugeta Belay; Gunnar Bjune; Fekadu Abebe (Taylor & Francis Group, 2015)
Background: TB-HIV co-infection is one of the biggest public health challenges in sub-Saharan Africa. Although there is a wealth of information on TB-HIV co-infection among settled populations in Africa and elsewhere, to our knowledge, there are no published reports on TB-HIV co-infection from pastoral communities. In this study, we report the prevalence of TB, HIV and TB-HIV co-infection among pulmonary TB suspects in the Afar Regional State of Ethiopia. Design: In a cross-sectional study design, 325 pulmonary TB suspects were included from five health facilities. Three sputum samples (spot-morning-spot) were collected from each participant. Sputum samples were examined for the presence of acid fast bacilli using Ziehl-Neelsen staining method, and culture was done on the remaining sputum samples. Participants were interviewed and HIV tested. Results: Of the 325 pulmonary TB suspects, 44 (13.5%) were smear positive, and 105 (32.3%) were culture positive. Among smear-positive patients, five were culture negative and, therefore, a total of 110 (33.8%) suspects were bacteriologically confirmed pulmonary TB patients. Out of 287 pulmonary TB suspects who were tested for HIV infection, 82 (28.6%) were HIV positive. A significantly higher proportion of bacteriologically confirmed pulmonary TB patients [40 (40.4%)] were HIV co-infected compared with patients without bacteriological evidence for pulmonary TB [42 (22.3%)]. However, among ethnic Afar pastoralists, HIV infections in smear- and/or culture-negative pulmonary TB suspects [7 (7.6%)] and bacteriologically confirmed pulmonary TB patients [4 (11.8%)] were comparable. On multivariable logistic regression analysis, Afar ethnicity was independently associated with low HIV infection [OR=0.16 (95% CI: 0.07-0.37)], whereas literacy was independently associated with higher HIV infection [OR=2.21 (95% CI: 1.05-4.64)]. Conclusions: Although the overall prevalence of TB-HIV co-infection in the current study is high, ethnic Afars had significantly lower HIV infection both in suspects as well as TB patients. The data suggest that the prevalence of HIV infection among Afar pastoralists is probably low. However, population-based prevalence studies are needed to substantiate our findings.